Digital Technology Development in the Form of YouTube Videos as Science Learning Media in Ecosystem Material on Learning Motivation - Nuriyah, Zidah Chotamy; Anggraini, Atika; Yusal, Yulianti; Sa'id, Ibrahim Bin; Maiyanti, Aziza Anggi; Wulandari, Ratna Wahyu (Indonesian Journal of Multidisciplinary Educational Research, 2023)
The development of digital technology is the result of engineering human reason, mind, and intelligence, which describes the progress of science and provides benefits in various aspects of human life. The research methods used were the ADDIE model. The ADDIE model is a methodically constructed learning design with certain stages in an effort to overcome learning problems and create reliable results. The results obtained were in the form of validity test results from several media, IT, material, and individual experts. The validity test results stated that animation-based YouTube video media was worth using. This YouTube video media could be used as a learning medium for grade VII students, creating a conducive learning atmosphere and motivate student learning.